Disturbance rejection and robust tracking control design for turbofan systems - Sakthivel, R.; Priyanka, S.; Kwon, O.M.; Mohanapriya, S.; Park, M.J. (Applied mathematical modelling, 2023)
•A resilient GESO based MRC control is designed to tackle the uncertainties and disturbances of turbofan systems.•The concise design of the control is developed by imposing the estimated disturbance on the control input channel.•The developed controller makes the state of the system to follow the given reference signal with accurate tracking.•Additive and multiplicative fluctuations are considered while designing the controller for better tracking performance.•The design procedure of the controller gain matrices are developed in the framework of linear matrix inequalities. The intention of this work is to analyse the issues of multiple disturbance estimation and rejection as well as robust tracking control design for turbofan systems subject to input gain perturbations. A standard generalized extended state observer is developed to estimate both the state disturbances and output measurement disturbances, simultaneously. Therewith, a modified repetitive controller is utilized with generalized extended state observer to track the states of the turbofan system accurately. Then, a new composite control strategy is developed by incorporating the estimates obtained via generalized extended state observer in modified repetitive controller to attenuate the effect of disturbances. Based on the pole placement technique, the observer gain is calculated and in accordance with Lyapunov stability theory, a set of sufficient conditions which ensures the robust asymptotic stability of the considered turbofan system is derived in the form of linear matrix inequalities. Moreover by offering the numerical examples with simulation results, the superiority of developed control strategy is validated.